The correlation sustainable development and population life quality for example Carpathians region - Химинець, Володимир Васильович (Technology audit and production reserves, 2014)
Today it is clear that any technical and technological innovation requires additional energy, raw material, it causes the emergence of additional quantities of waste and pollutants, so it causes stronger pressure on nature. It is necessary to take gradually a new world outlook - the ecological and economic paradigm - the idea of sustainable development - as a principle of the consumption of nature by the humanity. In the Carpathian region the rate of degradation of the "life sphere" is much faster than the rate of the awareness of this extremely dangerous process by the population and authority. The population of the Carpathian region is now living in the conditions of socio-economic discomfort, there have accumulated a lot of environmental, economic and social problems, solution of which requires the efforts of both, the state and public. The Sustainable Development Strategy provides that the productive forces, economic structure, specialization and location of output industries in the current conditions have to conform very close with the available natural resources, productive, reproductive and assimilative capacity of the environment. Moreover, the level and character of the usage of natural resources, especially land, water and mineral resources, the scale and direction of financial investment, the organization of technical, technological and organizational progress should be consistent not only with the current, but also with the perspective needs of the society.